Dinamika Spasial Permasalahan Transportasi di Demak: Perspektif Geografi Transportasi dalam Menghadapi Tantangan Banjir Rob dan Infrastruktur yang Terdampak di Wilayah Kabupaten Demak - Maarif, Muhammad Yusuf; Budiyanto, Eko (Jurnal Ilmiah WUNY, 2025)
Indonesia has very diverse topographical and geographical conditions. This gives rise to the frequent occurrence of natural disasters in several regions. One of them is Demak Regency, which is included in the North Coast of Java area and is located in lowlands, basins, and close to river flows. Tidal flooding disasters often hit the area, and certainly the occurrence of these disasters will impact several aspects. One aspect that is affected is the disruption of transportation network access. This article discusses the impact of tidal flooding on infrastructure conditions, particularly related to transportation in Sayung, Bonang, and Karang Tengah Districts of Demak Regency. The method used in writing this article is descriptive qualitative. Source collection was conducted through literature study or library research through various previous studies that can be accessed on the internet. The results of the research are Spatial Dynamics of Tidal Flooding, Impact of Tidal Flooding on Infrastructure and Transportation, Challenges in Facing Transportation Problems, and Solutions in Overcoming Transportation Problems.